2021
DOI: 10.21203/rs.3.rs-850531/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Melatonin Inhibits the Ferroptotic Pathway in Rat Bone Marrow Mesenchymal Stem Cells by Activating the PI3K-AKT-mTOR Signaling Axis to Attenuate Steroid-induced Osteoporosis

Abstract: ObjectivesSteroid-induced osteoporosis (SIOP) is a secondary osteoporosis, which is a systemic bone disease characterized by low bone mass, bone microstructure damage, increased bone fragility, and easy fracture. However, the specific mechanism remains unclear. Glucocorticoid-induced death of osteoblasts and bone marrow mesenchymal stem cells (BMSCs) is an important factor in SIOP. Ferroptosis is an iron-dependent programmed cell death that differs from apoptosis, cell necrosis, and autophagy, which can be ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Studies have confirmed that the disorder of PI3K/AKT signaling pathway is an important cause of the progress of osteoporosis. Some studies have pointed out that the activation of the PI3K/AKT signaling pathway can relieve steroid-induced osteoporosis by inhibiting bone mesenchymal stem cell wire [24]. In this study, path enrichment analysis found that the abnormal expression of MAP2K1, CCND2, CCND1, BDNF, INSR, AKT3, MYB, SGK1, FGF2 and FGFR1 is closely related to PI3K/AKT pathway imbalance.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Studies have confirmed that the disorder of PI3K/AKT signaling pathway is an important cause of the progress of osteoporosis. Some studies have pointed out that the activation of the PI3K/AKT signaling pathway can relieve steroid-induced osteoporosis by inhibiting bone mesenchymal stem cell wire [24]. In this study, path enrichment analysis found that the abnormal expression of MAP2K1, CCND2, CCND1, BDNF, INSR, AKT3, MYB, SGK1, FGF2 and FGFR1 is closely related to PI3K/AKT pathway imbalance.…”
Section: Discussionmentioning
confidence: 63%
“…PI3K/AKT signaling pathway is an intracellular signal transduction pathway, which also responds to extracellular signals and promotes cell proliferation, metabolism and growth. Its abnormalities are closely related to a variety of orthopedic diseases [22,23]. Studies have confirmed that the disorder of PI3K/AKT signaling pathway is an important cause of the progress of osteoporosis.…”
Section: Discussionmentioning
confidence: 94%